Situational Approach to Corruption Crimes Prevention: Forensic Aspect - I. E. Nikitina; M. G. Nersesyan; I. D. Sharapova (Теория и практика судебной экспертизы)
The article addresses modern ways countering corruption. Based on the analysis of foreign experience the major trends in improvement of national and international legal anti-corruption framework are presented. The development of a high level anti-corruption culture in a society, which relates directly to transparency, publicity and repudiation of this phenomenon across all levels of government, is shown to be one of the most effective ways. Reporting on all cases of corruption should be seen as any citizen’s civil duty since corruption is considered a threat to state of law institutions, democracy, human rights and social justice.The article presents the main legal and institutional models of corruption counteraction in modern countries. It is justified that, with the current level of technology development, appointment of forensic examinations is becoming the most prevalent investigative action. They are particularly relevant in cases involving corruption.